The yellow wallpaper [videorecording (Blu-Ray)] - Loreth, Alexandra; Loreth, Alexandra; Pontuti, Kevin; Mullins, Joe; O'Connor, Jeanne; Gilman, Charlotte Perkins, 1860-1935 (BayView Entertainment, 2023)
Jane, a writer and young mother, is prescribed a rest treatment by her physician husband John, who takes her to a remote country estate for the summer. She becomes obsessed with the peculiar yellow wallpaper in the bedroom he has chosen for her. In her isolation, she secretly writes about a woman trapped in the wallpaper that she must free.